'Altman Ζ-score model' and prediction of business failures. (7th November 2008) - Alexakis, Panayotis
This paper analyses whether Z-score, as examined by Altman and other researchers, can predict correctly company failures. The empirical analysis concentrates on the construction companies listed in Athens Exchange, for the period 1995-2006, which coincides with significant construction activity in Greece. It is investigated whether Z-score models can predict bankruptcies for a period up to eight years earlier. It is derived that a particular Altman model performs well in predicting failures for a period up to five years earlier. This is in line with other findings. The empirical results are interesting as they can be used by portfolio managers in stock selection and by company management for merger decisions or other corporate strategic moves.